Adult organotypic brain slice cultures recapitulate extracellular matrix remodeling in hemorrhagic stroke - Hewitt, Benjamin J.; Roberts, Lauren; Roberts, James A.; Fulton, Daniel; Hill, Lisa J.; Kitchen, Philip; Bill, Roslyn M.; Botfield, Hannah F. (Frontiers in Cellular Neuroscience, 2026)
Haemorrhagic stroke is a devastating condition characterized by vessel rupture and free blood within the brain parenchyma or cerebrospinal fluid (CSF) filled spaces. Across the major subtypes of hemorrhagic stroke (subarachnoid, intracerebral, and intraventricular hemorrhages), the presence of blood in the CSF generates significant tissue damage in the first 72 h after the event, known as early brain injury (EBI). EBI includes neuroinflammation, blood-brain barrier breakdown and dysregulation of extracellular matrix (ECM) dynamics. ECM dysfunction has been shown to trigger fibrosis of the cortical blood vessels, limiting normal CSF circulation and resulting in the buildup of metabolic waste or the development of post-hemorrhagic hydrocephalus. Limiting or preventing this fibrosis may therefore reduce the rate of morbidity experienced by survivors, providing a potential avenue for non-surgical treatment to reduce secondary brain injury post-stroke. Despite this, current in vivo approaches fail to differentiate between the effect of blood products and secondary consequences including intracranial pressure (ICP) elevation and mass effect. Here, we describe an adult rat organotypic brain slice culture (OBSC) model of hemorrhagic stroke which enables the identification of the effect of blood products on ECM dysregulation. We demonstrate the distribution of key cell types across a time course of 0, 3 and 7 days in culture, indicating that such cultures are viable for a minimum of 7 days. Using immunofluorescence staining, Western blotting and RNA sequencing, we show that exposure of OBSCs to lysed blood markedly increases ECM deposition around cortical blood vessels. This is accompanied by dysregulation of ECM regulatory genes and upregulation of inflammation and oxidative stress-related genes, successfully recapitulating the changes seen in human stroke survivors. This versatile ex vivo model provides a translational platform to further understanding of hemorrhagic stroke pathophysiology and develop or trial novel therapeutics prior to progression to in vivo stroke studies.